Satellite stellar refraction navigation using star pixel coordinates. Issue 1 (6th February 2019) - Ning, Xiaolin; Sun, Xiaohan; Fang, Jiancheng; Liu, Fucheng
Abstract: When stellar refraction occurs, the refraction apparent rays contain two kinds of refraction information, stellar refraction angle and stellar refraction direction. The refraction apparent height and the stellar refraction angle are two typical measurements used in stellar refraction navigation, which essentially only uses stellar refraction angle, and does not use stellar refraction direction. In fact, the stellar refraction direction is a function of the satellite position vector, which is useful in determining the satellite position. In this paper, a new stellar refraction navigation method using the star pixel coordinates as a measurement is proposed to improve navigation accuracy by using two kinds of refraction information at the same time. The corresponding measurement model for the star pixel coordinates is established. Simulations show that the proposed method's navigation performance is better than that of refraction apparent height and stellar refraction angle.